1973
DOI: 10.1002/cpt1973144part1552
|View full text |Cite
|
Sign up to set email alerts
|

Comparative drug elimination capacity in man‐glutethimide, amobarbital, antipyrine, and sulfinpyrazone

Abstract: The apparent elimination half-lifes were determined for 4 drugs that undergo hydroxylation in men. Glutethimide (500 mg), amobarbital sodium (130 mg), antipyrine (1.0 gm), and sulfinpyrazone (400 mg) were each taken orally by 10 healthy men at weekly intervals. When the half-lifes in these 10 individuals were compared, positive correlations were found among 3 out of 4 drugs: glutethimide-amobarbital (r 0.69, p < 0.05), glutethimide-sulfinpyrazone (r 0.64, p < 0.05), and amobarbital-sulfinpyrazone (r 0.87, p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…In previous studies, no significant relationship could be found between the halflife of antipyrine and the half-life of other drugs which are similarly metabolized by the mixed function oxidases, e.g. amylobarbitone, glutethimide, sulfinpyrazone, phenylbutazone, dicoumarol, aminopyrine, phenacetin, diazepam and quinine Davies, Thorgeirsson, Breckenridge & Orme, 1976;Kadar, Malsa, Endreyi, Johnson & Kalow, 1973;Vesell, Passananti, Greene & Page, 1971;Vesell & Page, 1968;Hepner, Vesell, Lipton, Harvey, Wilkinson & Schenker, 1977). In the above studies, however, elimination kinetics were generally compared in subjects with relatively homogeneous drug metabolizing capacity, such as normal volunteers selected from a uniform environment.…”
Section: Methodsmentioning
confidence: 95%
“…In previous studies, no significant relationship could be found between the halflife of antipyrine and the half-life of other drugs which are similarly metabolized by the mixed function oxidases, e.g. amylobarbitone, glutethimide, sulfinpyrazone, phenylbutazone, dicoumarol, aminopyrine, phenacetin, diazepam and quinine Davies, Thorgeirsson, Breckenridge & Orme, 1976;Kadar, Malsa, Endreyi, Johnson & Kalow, 1973;Vesell, Passananti, Greene & Page, 1971;Vesell & Page, 1968;Hepner, Vesell, Lipton, Harvey, Wilkinson & Schenker, 1977). In the above studies, however, elimination kinetics were generally compared in subjects with relatively homogeneous drug metabolizing capacity, such as normal volunteers selected from a uniform environment.…”
Section: Methodsmentioning
confidence: 95%
“…The drug most often used is antipyrine, and comparison of its plasma half-life in groups of subjects and in individuals before and after exposure to a drug has been valuable in assessing induction in man, and for investigating the genetic control of microsomal enzyme activity (Vessell and Page, 1969). On the other hand, the half-life of antipyrine does not always correlate well in an individual with the plasma half-lives of other drugs known to be metabolised by the microsomal detoxicating enzyme system (Kadar et al, 1973). It cannot be used to predict how an individual will respond to any other drug.…”
Section: Metabolism Of Exogenous Substancesmentioning
confidence: 99%
“…Table 5 summarises the results of sigma minus plots of the urinary excretion of sulphinpyrazone and its sulphone and parahydroxy metabolites (the minimum correlation coefficient for these plots was 0.979). The renal clearance of unchanged sulphinpyrazone and the sulphone appear in (Kadar et al, 1973) and 3.5 h for ten normal subjects (Senczuk & Jodynis-Liebert, 1979), both estimates being made from studies of urinary elimination kinetics. Shorter half-lives, 2.2 and 2.7 h, were found in two normal males given radiolabelled sulphinpyrazone by Dieterle et al (1975).…”
Section: Resultsmentioning
confidence: 99%